Curriculum for small-bowel capsule endoscopy and device-assisted enteroscopy training in Europe: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Sidhu, Reena; Chetcuti Zammit, Stefania; Baltes, Peter; Carretero, Cristina; Despott, Edward J.; Murino, Alberto; Dray, Xavier; Sanders, David S.; Keuchel, Martin; Dekker, Evelien; East, James E.; Johnson, Gavin; Pimentel-Nunes, Pedro; Arvanitakis, Marianna; Ponchon, Thierry; Dinis-Ribeiro, Mario; Bisschops, Raf (Endoscopy, 2020)
The European Society of Gastrointestinal Endoscopy (ESGE) has recognized the need to formalize training in small-bowel endoscopy across European centers. The following criteria and framework for training in small-bowel capsule endoscopy (SBCE) and device-assisted enteroscopy (DAE), which aim to provide uniform and high quality training to ensure that small-bowel endoscopists are competent to operate independently, are based on the current literature and experience of experts in the field. Three main areas are covered: skills required prior to commencing training in small-bowel endoscopy; structured training for trainees to become independent endoscopists; and ways of ensuring competence is achieved.1 Centers providing training in SBCE should perform a minimum of 75 – 100 SBCEs/year.2 Experience in bidirectional endoscopies is desirable for structured training in SBCE.3 SBCE courses should consist of at least 50 % hands-on training and cover information on technology, indications and contraindications for SBCE, pathologies that can be encountered on SBCE, and standard terminology that should be used during reporting of SBCE. An SBCE course should be completed prior to achieving competence in SBCE reporting.4 Competence in SBCE can be assessed by considering a minimum of 30 SBCEs. Direct Observation of Procedural Skills, short SBCE videos, and multiple-choice questions can be useful to assess improvement in the skills of trainees.5 Centers offering training in DAE should aim to carry out at least 75 DAEs/year, should have direct links with an SBCE service, and should allow regular discussion of cases at a radiology small-bowel MDT. Training centers with lower numbers are encouraged to offer training by “buddying-up” with other centers, or using mentoring systems.6 DAE trainees must be independent in bidirectional endoscopies and have experience in level 1 polypectomy prior to commencement of training. They should also be competent in reviewing SBCEs.7 Training in DAE should be structured with a minimum of 75 procedures, including 35 retrograde DAEs, with therapeutic procedures undertaken in at least 50 % of the DAEs performed. Training should cover the indications, contraindications, complications including prevention, and technicalities of the DAE procedure; formal evaluation should follow. DAE trainees must acquire skills to independently manage and advise on small-bowel pathology following DAE procedures.8 It is highly recommended that international societies develop online modules and courses on DAE, which are currently lacking across Europe.